KOCAK (Kopi Becak) Sebagai Solusi Perluasan Pemasaran Angkringan Kopi Kelana - Soebiyakto, Gatot; Finahari, Nurida; Gatut Rubiono (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
The food truck phenomenon has become a form of culinary business that is increasingly popular in various countries, including Indonesia. A food truck is a vehicle that is designed in such a way that it is suitable for selling food and drinks. KOCAK, namely a coffee rickshaw, a vehicle that can be said to resemble a mini food truck, but is specifically designed for the coffee angkringan model. This model is offered to partners of the 2024 PKM DRTPM program at Widya Gama University, Malang. The main marketing problem faced by partners is related to the sale of finished products. Sales of ready-to-drink coffee specifically produced by the partner community are constrained by the provision of angkringan locations, which require a lot of resources. Partners are targeting the existence of mobile angkringan. In this case, KOCAK is offered as a solution. This manuscript examines the potential success of the KOCAK design as a solution to partner problems. The results of the analysis of the KOCAK design show that KOCAK as an innovative design concept promises the potential for successful implementation when applied. Analysis of the components of the design plan has shown advantages in various aspects of the business. Thus, this solution is feasible to implement.